2021
DOI: 10.1007/s15010-021-01649-y
|View full text |Cite
|
Sign up to set email alerts
|

The proportion, species distribution and dynamic trends of bloodstream infection cases in a tertiary hospital in China, 2010–2019

Abstract: Background Recent epidemiological studies on bloodstream infection (BSI) that include the proportion, species distribution and dynamic changes are scarce in China. This study was performed to understand these epidemiological data of BSI over the past 10 years in China. Methods Using a prospective nosocomial infection surveillance system, this study was retrospectively performed in one of the largest hospitals in China. The time trend was tested using the C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
3
12
1
Order By: Relevance
“…Our main finding was that around 7% of hospitalized patients with COVID-19 may experience a BSI. This data was comparable with that measured among hospitalized patients prior to the pandemic [56]. Interestingly, around one out of three patients with COVID-19, once admitted to ICU, may have a clinical course complicated by a BSI.…”
Section: Discussionsupporting
confidence: 83%
“…Our main finding was that around 7% of hospitalized patients with COVID-19 may experience a BSI. This data was comparable with that measured among hospitalized patients prior to the pandemic [56]. Interestingly, around one out of three patients with COVID-19, once admitted to ICU, may have a clinical course complicated by a BSI.…”
Section: Discussionsupporting
confidence: 83%
“…In this case, neutropenia occurred after high-dose chemotherapy was performed for hematologic malignancy, which significantly impacts the incidence of bloodstream infection in cancer patients [ 21 ]. Furthermore, the patient was suggested to have a hospital-acquired bloodstream infection combined with the course of the disease, which was consistent with previous studies showing that the composition ratio of hospital-acquired bloodstream infections was increasing annually and those related to Enterobacterales also dynamically increasing [ 18 , 22 ].…”
Section: Discussionsupporting
confidence: 87%
“…Herein, P. faecalis was first found in China and presumptively associated with bloodstream infection. The prevalence of bloodstream infection increased from 2010 to 2019 in China, among which bacteremia occupied a dominant position (93.1%) [ 18 ]. Clinicians attached importance to patients suffering from bloodstream infection, given its high mortality, especially those with high disease severity and inadequate immunologic defenses [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is of note that the carbapenem resistance rates among the different bacterial isolation sites showed differences, such as the rates for carbapenem-resistant P. aeruginosa (CR-Pae) and carbapenem-resistant A. baumannii in bloodstream infections (BSIs) that were lower than those in respiratory infections ( Cai et al., 2017 ). In China, the proportions of Escherichia coli (9.8%–13.6%) and Klebsiella pneumoniae (5.3%–10.4%) in BSIs increased significantly from 2010 to 2019, while the proportion of P. aeruginosa decreased significantly from 4.0% to 2.4% ( Cui et al., 2021 ). Current evidence revealed that carbapenemase and β-lactamases combined with mutations that decrease permeability were associated with carbapenem resistance ( Queenan and Bush, 2007 ).…”
Section: Introductionmentioning
confidence: 99%